Pengkajian Aplikasi 3D untuk Permodelan Bangunan Bersejarah - Wijaksono, Sigit; Suryawinata, Bonny A.; Djimantoro, Michael Isnaeni (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Various history books as media to learn the history of Indonesia people are actually quite complete and adequate. However, the interest of younger generation, especially the children, to read the books is quite low. Additionally, the advance of computer technology makes kids and students more interested playing game than reading books. The game trend backgrounds the need for research on the use of computer game application as a medium to learn the history of the building through a game. As the special purpose of this research is to obtain a game application that can be a medium of learning historical buildings. The research is divided into two stages: the first stage is to identify gaming software that can be used as an educational game for historical buildings and to develop the model of 3D gaming applications; the second phase is the application trial and implementation at schools.